WOMEN AND PHYSICAL EDUCATION IN THE GLOBALIZED WORLD: THE CASE OF PE IN VIETNAM (Fiep Bulletin - online, 2014)
Vietnam has long endured intrusions by former Chinese dynasties and France, and the Vietnam War caused deterioration of safety and health of the people. Due to the Doi Moi policy in 1980s, Vietnam has excelled tremendously economically and educationally. However, unlike Japan, where the two authors reside, previous studies show that Physical Education in Vietnam has not been promoted strongly especially for female students. In this presentation, two authors have paid attention to Vietnam’s physical education, especially the relationship between women and PE, from the previous studies, from the comments and data of the interview and questionnaire we conducted for this study. Our findings show that PE in Vietnam has much room for improvement including facility, teaching method, and quality of PE teachers. Especially for female physical education, much need to be improved including philosophy behind it.
Keywords: PE; women; Vietnam; curriculum